(untitled) (JURNAL PENGMAS KESTRA (JPK), 2025)
As the elderly are getting older, this means they need special attention, especially in the areas of health and independence. Therfore, a way is needed to handle this problem so that it can be resolved immediately. By providing on healthy and independent elderly people by doing elderly gymnastics, this is one of the effort that is one of the efforts that can be made to solve this problem. The aim of this community service is to make the elderly aware of the importance of health, especially in old age. The community service methode used is by providing counseling followed by discussion sessions with the elderly to solve the health problems they are currently facing. The ecpected results of this community service is for the elderly know the benefits and importance of doing elderly gymnastics to maintain the health of the elderly. After this community service activity was held, especially the elderly are now willing to do physical activities independently and do elderly gymnastics regularly to improve their health. Thus, now the elderly can do their daily activities independently without expecting help from family or others. Therefore, it is necessary ti develop more useful and interesting activities, so that the elderly are more enthusiastic in increasing life expectancy and creating more productive and independent elderly.